2003
DOI: 10.1016/s0160-4120(03)00003-5
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in ambient air particles in the city of Las Palmas de Gran Canaria

Abstract: Concentration levels, seasonal variation and winter/summer ratios of 11 polycyclic aromatic hydrocarbons (PAHs) in the TSP of Las Palmas de Gran Canaria city were determined. The study area is under the influence of heavy traffic (80000 vehicles/day). Pyr/BaA, Pyr/Flt, B(ghi)P/I(cd)P and B(b+k)F/B(ghi)P ratios were calculated; the values of these two last suggest a strong influence of diesel fuel burning. Levels of TSP and TSP-bound PAHs were also established. The hazard potential of PAHs in terms of carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The ratio between them was from 0.5 and 1. Pristane can be found in biological material with pristane/ phytane ratio >> 1 (Alves 2008 (Castellano et al 2003;Fang et al 2004;Kalaitzoglu et al 2004), and in previous studies at the SPA site, BbF and Chr were the most abundant PAHs found (Cecinato et al 1997;Vasconcellos et al 2010).…”
Section: Extensive Campaignmentioning
confidence: 87%
“…The ratio between them was from 0.5 and 1. Pristane can be found in biological material with pristane/ phytane ratio >> 1 (Alves 2008 (Castellano et al 2003;Fang et al 2004;Kalaitzoglu et al 2004), and in previous studies at the SPA site, BbF and Chr were the most abundant PAHs found (Cecinato et al 1997;Vasconcellos et al 2010).…”
Section: Extensive Campaignmentioning
confidence: 87%
“…The BaP eq of individual B[a]P was more than half of that shown by the total PAHs. Other studies also showed that the carcinogenic potency of B[a]P is in the range of 27e67% of the carcinogenic activity of total PAHs (Petry et al, 1996;Castellano et al, 2003). Thus, B[a]P has been regulated in many countries and has a set guideline value.…”
Section: Pmf Modelmentioning
confidence: 99%
“…PAHs occur in both vapour and particulate phase in the atmosphere; both types can come into contact with living beings either externally (through the skin) or internally (through the lungs or ingestion) and this makes them hazardous or even toxic species [4,11]. The partitioning of a given compound between the particulate and the gas-phase depends on the ambient temperature, the nature (i.e.…”
Section: Introductionmentioning
confidence: 99%